2017
DOI: 10.1111/tri.12906
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal organ procurement in the Netherlands - an analysis of quality and clinical impact

Abstract: Between March 2012 and August 2013, 591 quality forms were filled out for abdominal organs in the Netherlands. In 133 cases (23%), there was a discrepancy between the evaluation from the procuring and transplanting surgeons. Injuries were seen in 148 (25%) organs of which 12 (2%) led to discarding of the organ: one of 133 (0.8%) livers, five of 38 (13%) pancreata and six of 420 (1.4%) kidneys (P < 0.001). Higher donor BMI was a risk factor for procurement-related injury in all organs (OR: 1.06, P = 0.011) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 19 publications
3
48
0
Order By: Relevance
“…However, when donor surgeons avoid in situ portal flush, for example, as in other countries, portal perfusion is immediately applied on the bench after hepatectomy, and a randomized comparison between in situ portal flush and bench portal flush has not yet been performed . Next, the 27.1% rate of liver injuries in our study paralleled recent results from the Netherlands, where de Boer et al demonstrated a higher risk of liver injuries in the setting of DCD donation surgery compared with DBD liver donation . Despite the relatively high rate of liver injuries, the authors found a low discard rate and no impact on graft survival .…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…However, when donor surgeons avoid in situ portal flush, for example, as in other countries, portal perfusion is immediately applied on the bench after hepatectomy, and a randomized comparison between in situ portal flush and bench portal flush has not yet been performed . Next, the 27.1% rate of liver injuries in our study paralleled recent results from the Netherlands, where de Boer et al demonstrated a higher risk of liver injuries in the setting of DCD donation surgery compared with DBD liver donation . Despite the relatively high rate of liver injuries, the authors found a low discard rate and no impact on graft survival .…”
Section: Discussionsupporting
confidence: 75%
“…(25) Next, the 27.1% rate of liver injuries in our study paralleled recent results from the Netherlands, where de Boer et al demonstrated a higher risk of liver injuries in the setting of DCD donation surgery compared with DBD liver donation. (26) Despite the relatively high rate of liver injuries, the authors found a low discard rate and no impact on graft survival. (26) In contrast, in our DCD cohort, injured livers had a higher risk for graft loss in high-risk and futile donor-recipient combinations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…for pancreas, 34 but the rate of discard resulting from surgical injury for these organs is 0.8-1.4% for kidney, 32,35 .8-6.6% for liver, 33,35 and 10-13% for pancreas. 35,36 Thus, these data indicate that albeit common, procurement-related injury is rarely irremediable or transplant-defining.…”
Section: P-valuementioning
confidence: 99%
“…Additionally, once procured, a fibrinolytic preflush such as tissue plasminogen activator (tPA) can be employed to decrease ischemic‐type biliary lesions, which is hypothesized to function by reducing peribiliary microvasculature microthrombi . In an analysis of organ procurement in the Netherlands, it was found that both higher BMI and procurement from a DCD donor were risk factors for increased procurement injury, further suggesting the need for experienced transplant surgeons . Finally, the cold ischemia time should be minimized with expedited graft allocation and transportation.…”
Section: Recent Improvements In Dcd Liversmentioning
confidence: 99%